Thermally activated delayed fluorescence exciplex emitters for high-performance organic light-emitting diodes - Zhang, Ming; Zheng, Cai-Jun; Lin, Hui; Tao, Si-Lu (Materials horizons, 2021)
Owing to their natural thermally activated delayed fluorescence (TADF) characteristics, the development of exciplex emitters for organic light-emitting diodes (OLEDs) has witnessed booming progress in recent years. Formed between electron-donating and electron-accepting molecules, exciplexes with intermolecular charge transfer processes have unique advantages compared with unimolecular TADF materials, offering a new way to develop high-performance TADF emitters. In this review, a comprehensive overview of TADF exciplex emitters is presented with a focus on the relationship between the constituents of exciplexes and their electroluminescence performance. We summarize and discuss the latest and most significant developments of TADF exciplex emitters. Notably, the design principles of efficient TADF exciplex emitters are systematically categorized into three systems within this review. These progressive achievements of TADF exciplex emitters point out future challenges to trigger more research endeavors in this growing field. Owing to their natural thermally activated delayed fluorescence (TADF) characteristics, the development of exciplex emitters for organic light-emitting diodes (OLEDs) has witnessed booming progress in recent years.